Health and its significance in the modern concept of wellness and spa - Kupcewicz, Ewa; Bentkowska, Aleksandra (Journal of Education, Health and Sport, 2023)
The aim of the study is to present selected issues related to health that are significant in the modern concept of wellness and spa. The World Health Organization has adopted the so-called positive definition of health, which encompasses it as a state of complete physical, mental, and social well-being, rather than merely the absence of disease or infirmity. Wellness is one of the contemporary approaches to health related to quality of life and actions for health (aspiring towards wellness). On the other hand, spa is an idea of a holistic approach to health, where the harmony of mind and body is to be ensured through the use of relaxing, cosmetic, and biological renewal treatments, often involving water. Spa centers combine relaxation with the care for psychophysical health. The purpose of these centers is to improve health, well-being, and appearance. These aspects are extremely important in the holistic understanding of health.